THE FOUNDATION OF THE SERBIAN SCHOOL OF GEOPOLITICS - Budimir, Zeljko; Stepić, Milomir (Politeia, 2019)
Practical geopolitics has long since existed in Serbian tradition; however, it has not developed enough in the scientific sense. The true beginnings of Serbian geopolitical thought can be found in the anthropogeographical works of Jovan Cvijić during the first decades of the 20th century, and his engagement in the formation of the South Slavic state. Afterwards, there is a long discontinuity, especially noticeable after the Second World War due to the Nazi misuse of geopolitics. The renaissance and the true development of Serbian geopolitics happens because of existential national causes – when the Serb issue is opened again, during the disintegration of Yugoslavia and in unfavorable international circumstances. Since then, four generations of geopolitical experts have matured, in whose research there is a specific common scientific approach, and one can conclude that an authentic Serbian geopolitical school is emerging. Its basic characteristics are that it is possibilistic, telurocratic, integralist, regionalist (Balkanic), and multidisciplinary, and that it has established its own terminology, alongside the universal one. Further progress of the Serbian geopolitical school will depend on the respect it garners in political-diplomatic practice, its position in the educational-scientific system, on adequate media promotions and successful suppression of trivialisation.